2006
DOI: 10.1007/s11325-006-0074-x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for activation of nuclear factor kappaB in obstructive sleep apnea

Abstract: Obstructive sleep apnea (OSA) is a risk factor for atherosclerosis, and atherosclerosis evolves from activation of the inflammatory cascade. We propose that activation of the nuclear factor kappaB (NF-kappaB), a key transcription factor in the inflammatory cascade, occurs in OSA. Nine age-matched, nonsmoking, and non-hypertensive men with OSA symptoms and seven similar healthy subjects were recruited for standard polysomnography followed by the collection of blood samples for monocyte nuclear p65 concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 27 publications
(29 reference statements)
1
32
0
5
Order By: Relevance
“…NF-kB is the master regulator of an inflammatory response and numerous inflammatory genes, such as TNF-a, IL-8 or ICAM-1, which are also known to be pro-atherogenic, are under its control. NF-kB activation has been demonstrated in cardiovascular tissue from mice treated with intermittent hypoxia and in cultured monocytes from OSA patients [61,62]. Using a cell culture model of intermittent hypoxia, RYAN et al [63] demonstrated a preferential activation of NF-kB-dependent proinflammatory pathways by intermittent hypoxia over adaptive hypoxia-inducible factor (HIF)-1 mediated pathways, which is in contrast to sustained hypoxia where adaptive pathways predominate.…”
Section: Systemic Inflammationmentioning
confidence: 99%
“…NF-kB is the master regulator of an inflammatory response and numerous inflammatory genes, such as TNF-a, IL-8 or ICAM-1, which are also known to be pro-atherogenic, are under its control. NF-kB activation has been demonstrated in cardiovascular tissue from mice treated with intermittent hypoxia and in cultured monocytes from OSA patients [61,62]. Using a cell culture model of intermittent hypoxia, RYAN et al [63] demonstrated a preferential activation of NF-kB-dependent proinflammatory pathways by intermittent hypoxia over adaptive hypoxia-inducible factor (HIF)-1 mediated pathways, which is in contrast to sustained hypoxia where adaptive pathways predominate.…”
Section: Systemic Inflammationmentioning
confidence: 99%
“…Activation of transcription factors in OSAHS and in animal models of IH NF-kB and AP-1 Activation of inflammatory pathways by upregulation of NFkB was demonstrated in neutrophils and monocytes of patients with OSAHS [84][85][86], and in an in vitro model of HeLa cells treated with IH [87]. Consequently, upregulation of adhesion molecules and inflammatory cytokines and adipocytokines, the gene products of NF-kB, were also noted, further supporting activation of NF-kB in OSAHS [57,67,88,89], as well as in associated conditions and comorbidities [90].…”
Section: Ros As Signalling Moleculesmentioning
confidence: 99%
“…In addition, these alterations can turn on nuclear transcriptional factors, including nuclear factor-B, which induce production of inflammatory mediators, intracellular and vascular cell adhesion molecules [12] . All the above could facilitate vascular endothelial damage and atherogenesis [13][14][15] . In this way, intermittent hypoxia may lead to atherosclerosis and, ultimately, the cardiovascular consequences of OSAS.…”
Section: Activationmentioning
confidence: 99%